(untitled) (Journal of Architectural Design, 2023)
In given article we will try to analyze the beginning of Mughal architecture. Moreover, we will try to clear up the role of Babur in formation of Mughal architecture. Lastly, we describe how Baburs early buildings has been created and its development over the years, also, we have given an evidence supporting our points.